Effects of an enriched physical activity programme on selected anthropometric, physiological and performance characteristics of an underprivilieged ethnic group - Van Rooyen, Frederick (Rhodes University, Faculty of Science, Department of Human Movement Studies, 1994)
Fifty pre-pubescent Xhosa-speaking children from two primary schools within the township of Rini, Grahamstown, were selected in this study to determine the effects, if any, of an enriched physical activity programme. Subjects were divided into experimental and control groups with only the experimental group physically participating in the enrichment programme. Selected anthropometric, physiological and motor performance tests were administered on both groups, before and after the programme, to monitor the effect of the enrichment programme on growth, cardiovascular efficiency and physical performance. Somatotype ratings showed no change after the training programme. However body composition showed greater gains in fat mass in the control group and marked drops in fat mass and increases in lean body mass in the experimental group. Longer running distances, higher predicted VO2 max mean values and improved recovery heart rate (HR) as well as larger gains in relative power, absolute power and velocity were experienced by individuals who participated in the training programme. The performance of the experimental group in the two motor performance tests out-weighed by far the performance of the control group as a result of the additional programme. The enrichment programme not only produced a positive effect on body composition but also improved aerobic and anaerobic efficiency. Improvements in both motor performance tests favoured the experimental group.
Keywords: Uncatalogued